THE DEVELOPMENT OF READING LEARNING MATERIAL BASED ON DRTA STRATEGY AS AN EFFORT TO BUILD A LITERATE GENERATION IN FIFTH GRADE (5th) OF PRIMARY SCHOOL - Faisal, Faisal; Lova, Stelly Martha (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to develop reading learning materials based on DRTA strategy (Direct Reading Thinking Activity) as an effort to build a literate generation in 5th Grade of Primary School. It is well known that the literacy study is one part of the implementation policy of the 2013 curriculum in primary school. This policy implies that the learning process implemented so far has not been able to adopt the optimal process of literacy learning. There are three main requirements to be considered in the development research conducted, such as; the validity, practicality and effectiveness of teaching materials developed. The development model used is a 4-D model, namely: define, design, development and disseminate. The results showed that the developed teaching materials declared were valid, practical and effective to use in the reading learning process of 5th grade in Primary School. Thus, the use of DRTA-based teaching materials in reading learning deserves to be considered as an effort to build literate generation in 5th Grade of Primary School.Keywords: teaching material, reading, DRTA Strategy, literate generation